Cryo-ablation management of atrial fibrillation in Fabry disease without agalsidase alpha: a case report - Yuanzhu Li; Yuanzhu Li; Bi Huang; Bi Huang; Suxin Luo; Suxin Luo (Frontiers in Cardiovascular Medicine)
Fabry disease (FD) is a rare genetic disorder caused by mutations in the GLA gene, affecting multiple organs. Over 60% of patients experience heart-related issues, primarily arrhythmias. Unlike typical cases, these arrhythmias are complex and often do not respond well to standard antiarrhythmic drugs, sometimes worsening symptoms. This paper presents a case study of a FD patient with paroxysmal atrial fibrillation successfully treated using bilateral pulmonary vein cryoablation, resulting in positive outcomes. Additionally, we conducted molecular docking studies for the first time to assess the enzyme-substrate binding of E358del, confirming findings similar to laboratory experiments. Our findings underscore the potential role of artificial intelligence in better understanding FD, and aim to provide insights into managing arrhythmias associated with FD.